Challenging the Sacred: the Fatwa of the Indonesia Ulama Council on the Recitation of Translation During the Prayer - Syahril Siddik (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2014)
This article examines the fatwas of the MUI (Indonesian Ulama Cuncil) on the recitation of translation during the Prayer. The MUI fatwas were in response to the new trend of reading Indonesian language during prayer among Indonesian Muslims. In Islam, the practice of worship (praying) has been regulated by and based on the tradition of the Prophet Muhammad Saw. Debates over the issues whether or not praying can be performed in local language arose when Muhammad Yusman Roy form Surabaya initiated the practice of praying by reciting Bahasa Indonesia instead of Arabic. The author presents different views among classical Islamic scholars (ulama) about the translation of shalat recitation and explains why the MUI has forbid this practice in the Indonesian context. Keywords: prayer, MUI, fatwa, ijtihad, innovation (bid’ah)